Teorema Titik Tetap untuk Pemetaan Kannan dan Chatterjea pada Ruang Metrik Modular Bernilai Kompleks - Mariatul Kiftiah; Yudhi Yudhi (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2023)
In this paper, inspired by fixed point concepts of complex valued modular metric space, we introduce Kannan complex and Chatterjea complex mappings. Using this new idea, some fixed point theorems involving both of these contractive mappings are established. Furthermore, existence and uniqueness of fixed point for Kannan complex and Chatterjea complex mappings on complex valued modular metric space is proved.